The effect of fertilization on growth, in diameter and height, of Pinus caribaea in plantations of western Cuba - León Sánchez, María Amparo; Reyes Pozo, Jorge Luis; Herrero Echevarría, Grisel; Pérez Léon, Victor Ernesto (Instituto de Ecología, A.C., 2016)
Some studies focus on the analysis of the effect of mineral fertilization on variables associated with tree growth in productive plantations. They mainly analyze the short-term response to fertilization. The aim of this research is therefore to analyze the long-term response to mineral fertilization, applied fractionally over the first five years of the establishment of a Pinus caribaea plantation in Viñales, Pinar del Río, Cuba. The effect on growth, in diameter and height, was examined using a randomized block design. Seven treatments were established, according to the doses and application regime of NPK, as well as a control, with no fertilizer. These variables were measured at different ages, in 288 trees over 41 years and the growth functions were estimated using a multilevel regression for the entire period and in two separate stages. The analysis of the coefficients for the obtained growing curves showed that, in the period from 2 to 41 years, the diameter and height for individual trees were, on average, superior to those of the control, in treatments of 600 g, 800 g and 1000 g of Nitrogen, Phosphorus and Potassium (NPK) per tree. Treatment with application of a single dose of 300 g of Nitrogen, Phosphorus and Potassium (NPK) tree-1 produced lower values of diameter and height than those of the control. The two-stage study demonstrated that, from 33 to 41 years, homogeneity in height was achieved among treatments, except for the treatment with 300 g of (NPK) tree-1, which presented lower heights relative to those of the control.